From Social Media to Socio-Political Change: How Gen Z Drives Political Reform in Bangladesh - Omi, Maidul Islam Omi; Islam, Mohibul; Shahanaz Akter; Suraiya, Suraiya (Technium Social Sciences Journal, 2025)
This research explores the role played by social media in stimulating socio-political transformation, focusing on the Boishommo Birodhi Chatra Andolon 2024—a youth-led anti-discrimination movement in Bangladesh. Using qualitative methods, the research draws on thirty unstructured interviews, including twenty-five activist interviews and five key informant interviews with coordinating Somonnoyok and movement leaders in charge of the digital front, to understand the role played by social media in mobilizing such a movement. Thematic analysis of the interviews demonstrates how social media, including Facebook, Telegram, and WhatsApp, played the most critical role in decentralized network creation, collective identity-making, and giving voice to marginalized voices. Guided by a multi-theoretical framework—including Networked Social Movements, the Elaboration Likelihood Model, Intersectionality, and Tactical Digital Activism—this study explains how digital tools shaped activist strategies and identities. With strategic deployment of central and peripheral influence strategies, activists successfully addressed broad audiences. In the face of challenges like internet shutdowns, censorship, and digital monitoring, the movement proved resilient, using end-to-end-addressed tools and offline strategies to maintain its decentralized network. Social media became not merely a communication device—it became a site of emotional support, acts of culture-making, and digital counter-action. In conclusion, findings highlight the promise of hybridized activist models integrating digital advocacy with ground-level mobilization. This study concludes by proposing support for ethical digital action, access for all, and reform in related policymaking to consolidate participatory democracy. This study foregrounds a digitally native generation that is making new politics in the Global South converge through networked, intersectional, and participatory practices.